Implementation of LoRaWAN on Energy Monitoring System on the Onion Leaf Pest Light Trap device - Enriko, I Ketut Agung; Kuswanda, Kuswanda; Kurnianto, Danny; Gustiyana, Fikri Nizar (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Shallot cultivation is a significant livelihood for farmers due to the high selling value of the harvest. However, most farmers still control shallot pests by excessively spraying pesticides, leading to concerns about excess residue on the plants. Physical control methods, such as installing light traps on plantations, have been attempted, but their manual operation is inefficient for farmers' working time and prone to wasting electrical energy due to negligence. In this research, the light trap will be optimized by implementing an automatic light monitoring and control system, allowing farmers to estimate the cost of electricity used and adjust usage according to their needs. The LYNX32 BOARD LoRa plays an important role as a data processor, connected to the LDR sensor to enable automatic light activation, and the PZEM-004T sensor to monitor the voltage and current of the light trap, transmitting this data via LoRa communication. In this research, automatic control operates based on the light intensity, and LoRa can transmit data up to a distance of 250 meters under line-of-sight (LOS) conditions. The PZEM-004T sensor has good accuracy for voltage, with an error of 0.08%, while the error percentage for current and power is 13.26% and 5%, respectively.